2013
DOI: 10.1097/mao.0b013e31827853c3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between 2 Laser Systems, Er-Yag and CO2, in Stapes Surgery

Abstract: To sum up, our observations have proven the usefulness of 2 laser systems: CO2 and Er-Yag lasers in stapes surgery. In both groups, a decrease in the hearing threshold was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In 1999, Hausler first reported the application of an erbium-doped yttrium aluminum garnet (Er:YAG) laser system in stapedotomy and obtained positive results, with an air-bone gap (ABG) of less than 20 dB in 15 cases (ears) [10] ; similar findings were first reported in China in 2004. The usefulness of both CO 2 and Er:YAG lasers in stapes surgery have been confirmed with a decrease in the hearing threshold [11] . The 3-year follow-up of patients who received laser treatment showed that the Er:YAG laser was the safest type of pulsation laser for use in ear surgery because no facial nerve paralysis or adverse effects were observed in the inner ear function [12] .…”
Section: Introductionmentioning
confidence: 82%
“…In 1999, Hausler first reported the application of an erbium-doped yttrium aluminum garnet (Er:YAG) laser system in stapedotomy and obtained positive results, with an air-bone gap (ABG) of less than 20 dB in 15 cases (ears) [10] ; similar findings were first reported in China in 2004. The usefulness of both CO 2 and Er:YAG lasers in stapes surgery have been confirmed with a decrease in the hearing threshold [11] . The 3-year follow-up of patients who received laser treatment showed that the Er:YAG laser was the safest type of pulsation laser for use in ear surgery because no facial nerve paralysis or adverse effects were observed in the inner ear function [12] .…”
Section: Introductionmentioning
confidence: 82%
“…The ABG closure was calculated using the four-tone average for pre- and post-operative air conduction and bone conduction thresholds in 86.3 per cent of the papers; 4 , 6 , 7 , 14 21 , 23 53 , 55 , 59 , 62 however, 3 kHz was only used in 45.1 per cent of these calculations 6 , 7 , 15 , 16 , 20 , 21 , 24 , 28 , 32 34 , 38 , 40 44 , 47 , 51 , 53 , 55 , 57 , 59 . The remaining papers either substituted 3 kHz with 4 kHz (in 79.2 of papers), or averaged 2 kHz and 4 kHz (in 16.7 per cent).…”
Section: Discussionmentioning
confidence: 99%
“…The pulse energy for Er:YAG laser used for stapedotomy ranges from 10 to 450 mJ in the literature ( 20 , 29 ). The upper limit of pulse energy differs between authors.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue with high water content can be ablated precisely with no or minimal thermal effect to the inner ear ( 10 ). Several clinical studies have demonstrated the feasibility and efficiency of the Er:YAG laser in stapes surgery ( 20 ). However, at the same time, the Er:YAG laser produces acoustic shock waves causing explosive ablation of bone and generates a shockwave through the inner ear, which can potentially harm inner ear function ( 10 , 21 ).…”
mentioning
confidence: 99%